Investigation of surface effects on ice formation - He, Zijing (Nanyang Technological University, 2022)
The accumulation of ice can cause disasters in aircrafts. It can occur when aircraft are on the ground and in the flight. The methods, such as the use mechanical tools, apply hot water, and use infrared heating, are only applicable to certain situations. Therefore, to fully prevent accidents to occur due to ice formation, it is necessary and important to investigate the relationship between hydrophobic surfaces and anti-icing properties. One of the most effective methods in fabricating hydrophobic surfaces is chemical etching. The 6061 Aluminium Alloy is used in this project to simulate an aircraft surface as it is easy to be welded and manipulated. Besides that, it is also very light and fairly strong, which makes it ideal for aircraft wings. In this study, they were chemically etched by using Sodium Hydroxide (NaOH) as etchant and to obtain different contact angles. The project consists of preliminary experiment (without submersion), 1st submersion (30mins), 2nd submersion (30mins) and 3rd submersion (1hr). Preliminary experiments were conducted to obtain the critical etching duration and etchant concentration that will produce the ideal hydrophobic surface. Next, the submersion experiment was carried out to simulate the condition when there is a rain before and after the aircraft took off. These samples will be submerged for 3 durations of: a) 30min; b) 30min; c) 1 hr, which is used to determine if the superhydrophobic properties is still present after submersion. Lastly, an experiment was designed to measure the time from starting of the ice formation to complete freezing. From the results that were obtained from above experiments, the critical etching duration and etchant concentration is 2M NaOH for 2.5 min & 0.5M NaOH for 6 min which produced a contact angle of 161.85°. This test plate produced the largest contact angle of 161.85° and had the slowest ice formation time of 512 sec. However, the ice formation time decreased after each submersion, and the time decreased to 354 sec after all submersion experiments.